(untitled) (The Review of Diabetic Studies, 2024)
Background: The healthcare workforce in Saudi Arabia is experiencing a period of rapid transformation as part of the Kingdom’s Vision 2030 initiatives aimed at achieving sustainable healthcare delivery. Despite significant advancements in healthcare infrastructure and technology, challenges such as workforce shortages, uneven regional distribution, burnout, and continued reliance on expatriate professionals persist. These factors affect workforce sustainability and the quality of healthcare services. Aim: This systematic review aims to explore the key challenges and emerging opportunities influencing the healthcare workforce in Saudi Arabia and to identify strategies that support sustainable workforce development in alignment with national health transformation goals. Method: A systematic review was conducted following PRISMA guidelines. Literature published between 2020 and 2024 was searched across major databases, including PubMed, Scopus, ScienceDirect, Google Scholar, and national repositories. A total of 345 studies were retrieved, screened for relevance, and assessed for methodological quality. Ten high- and moderate-quality studies were included for thematic synthesis. Results: The review identified four major themes: workforce shortages and distribution, burnout and well-being, education and professional development, and healthcare transformation under Vision 2030. Findings indicated steady progress in workforce training, leadership development, and digital innovation, though persistent shortages and job dissatisfaction remain major concerns. Conclusion: Saudi Arabia’s healthcare workforce is evolving toward sustainability through modernization, professional education, and reform-driven innovation. Continuous investment in training, retention strategies, and policy integration is essential to achieving a resilient and future-ready workforce.